The Impact of Team Quiz Method on Students' Ability to Solve Higher Order Thinking-based Questions in Social Studies Learning - Eliana, Neneng; Ambar Wati, Unik (Journal for Lesson and Learning Studies, 2024)
The lack of precise application of learning methods causes students' low ability to solve Social Sciences questions based on higher-order thinking Skills (HOTS). Therefore, appropriate learning methods are needed as a solution to overcome this problem. The research aimed to test the effect of applying the Team Quiz method on students' ability to solve HOTS-based social studies questions on ASEAN material. This research uses a quasi-experimental method with a pretest-posttest nonequivalent control group design. The research sample consisted of 36 students distributed into 2 classes. Data collection techniques through tests. Data analysis techniques using parametric statistics through normality tests, homogeneity tests, and hypothesis tests. The results showed that the Shapiro-Wilk normality test was > 0.05 and the homogeneity test had a significant value (Sig.) > 0.05. This means that the research data is normally distributed and the two groups have the same level of variance. Hypothesis test results (Independent Sample T-Test) with a sig value. (2-tailed) 0.000 < 0.05. The average N-Gain score in the experimental class was 63.99% with a minimum score of 53.33 and a maximum score of 80.00, included in the quite effective category. On the other hand, the average N-Gain score in the control class was only 23.37% with a minimum score of 15.38 and a maximum score of 38.46, included in the ineffective category. Thus, it can be concluded that there is a significant influence of the application of the Team Quiz method on students' ability to solve HOTS-based social studies questions on ASEAN material.